Disruption and collaboration in digital journalism: ambivalence of social responsibility and political economy practices of media companies - Mufti Nurlatifah,; Nina Mutmainnah, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Digitization encourages journalism to transform. Since the development of digital media, communication and media scholars have predicted journalism to develop at two levels. First, journalism evolves along with technological developments and is involved in media disruption. Second, journalism sticks with professionalism and establish technology as a tool to realize social responsibility. Today we are dealing with the transformation in journalism that we get from disrupted contents, disrupted media companies, and collaboration among media institutions. Various digital journalism platforms have emerged as a manifestation of the diversity of content and diversity of media ownership. This was an exploratory study that aimed to explain collaborations among various media in the digital ecosystem. The focus of this study was to map media networks through media data distributed in various official media or regulators. The results of this study showed that in a digital ecosystem that promises many opportunities, digital journalism still has to deal with the dilemma between social responsibility and the political economy of media. On the one hand, digital journalism faces disruption which serves as a significant factor that encourages journalism to transform. On the other hand, digital journalism also deals with a natural selection that forces them to collaborate, i.e. a manifestation of the political economy of media.